The Influence of the Role of the School Committee, Work Discipline, and School Leadership on Improving the Quality of Education in Public Junior High Schools in Banyumas Regency - Chrisandi, Arsand; Yuliejatiningsih, Yovitha; Rasiman, Rasiman (Journal of Educational Sciences, 2025)
The quality of education is a crucial factor in determining the progress of a nation, thus requiring continuous improvement through the active involvement of various stakeholders. In Indonesia, the role of school committees, the work discipline of educators, and the leadership of school principals are considered strategic elements in enhancing educational outcomes, especially in public junior high schools where collaboration with the community plays an important role. This study aims to analyze the influence of school committee roles, work discipline, and principal leadership on improving the quality of education in public junior high schools in Banyumas Regency. The research employed a quantitative approach with simple linear regression analysis and hypothesis testing. A total of 144 respondents participated in the study, consisting of both civil servant and contract teachers. The results show that the three variables significantly affect the quality of education, with a simultaneous contribution of 25.7%. The findings highlight that synergy among school committees, teacher discipline, and school leadership is essential to achieving better educational performance and sustainable quality improvement.